Legislation of direct-to-consumer genetic testing in Europe: a fragmented regulatory landscape - PHILLIPS, ANDELKA (My University, 2017)
Despite the increasing availability of direct-toconsumer (DTC) genetic testing, it is currently unclear how such services are regulated in Europe, due to the lack of EU or national legislation specifically addressing this issue. In this article, we provide an overview of laws that could potentially impact the regulation of DTC genetic testing in 26 European countries, namely Austria, Belgium, Cyprus, the Czech Republic, Denmark, Estonia, Finland, France, Germany, Greece, Hungary, Ireland, Italy, Latvia, Lithuania, Luxembourg, Norway, Poland, Portugal, Romania, Slovakia, Slovenia, Spain, Sweden, the Netherlands and the United Kingdom. Emphasis is placed on provisions relating to medical supervision, genetic counselling and informed consent. Our results indicate that currently there is a wide spectrum of laws regarding genetic testing in Europe. There are countries (e.g. France and Germany) which essentially ban DTC genetic testing, while in others (e.g. Luxembourg and Poland) DTC genetic testing may only be restricted by general laws, usually regarding health care services and patients’ rights.
PUBLISHED
joint author with Louiza Kalokairinou et al, ?Legislation of Direct-to-Consumer Genetic Testing in Europe: A Fragmented Regulatory Landscape? ? this has been submitted to the Journal of Community Genetics. ? This has a large number of authors because it reviewing the law in a large number of European Member States.
Keywords: direct-to-consumer genetic testing; personal genomics; privacy; informed consent; data protection; medical devices; IVD; Genes & Society